2020
DOI: 10.1002/cite.202000135
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Visualization of Internal and External Concentration Fields in Multiphase Systems via Laser‐induced Fluorescence and Rainbow Schlieren Deflectometry During and After Droplet Production

Abstract: The applicability of laser‐induced dye fluorescence (LIF) and rainbow schlieren deflectometry (RSD) for qualitative, non‐invasive real‐time visualization of spatial concentration distributions in two standard reference systems is presented. The combination of LIF and RSD enables measurements inside and outside of droplets and is able to overcome limitations of both measurement techniques. Experimental results in the presence of interfacial phenomena are compared and the connection between inner and outer effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition, since the release and establishment of said document, significant progress has been achieved, especially in terms of measurement technology. (Laser-)Optical methods such as particle image velocimetry (PIV) [3,4], laser induced fluorescence (LIF) [5][6][7] and the shadowgraphy method [8,9] have become the standard for fluid flow investigation, alongside numerical simulations via computational fluid dynamics (CFD) [10][11][12][13][14][15]. Internationally, the encyclopedic Handbook of Industrial Mixing has been published, documenting the progress in understanding mixing processes in recent decades and providing at least some basic construction guidelines for multistage impellers [16,17].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition, since the release and establishment of said document, significant progress has been achieved, especially in terms of measurement technology. (Laser-)Optical methods such as particle image velocimetry (PIV) [3,4], laser induced fluorescence (LIF) [5][6][7] and the shadowgraphy method [8,9] have become the standard for fluid flow investigation, alongside numerical simulations via computational fluid dynamics (CFD) [10][11][12][13][14][15]. Internationally, the encyclopedic Handbook of Industrial Mixing has been published, documenting the progress in understanding mixing processes in recent decades and providing at least some basic construction guidelines for multistage impellers [16,17].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…46 In this line, the recent studies based on noninvasive techniques, viz. confocal Raman spectroscopy, 14 planar laserinduced fluorescence, 11,13 Schlieren optical method, 12 etc., contribute to the improved understanding in terms of visualization of interfacial flow and concentration field in the drop. Common observation is that the interfacial instability is more prone to occur at higher initial concentrations of the solute and, thereby, results in the greater mass transfer due to a higher surface renewal rate of the solute at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that 10–50% and even 80% of the overall mass transfer occurs during drop formation, due to the very high concentration gradient in this stage. Thus, with the aim of evaluating early-stage mass transfer coefficient, the formation of a single drop has been studied by a few authors, using experiments, analytical models, and recently, numerical simulations. …”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the transferring component has an additional and undefined reservoir within the capillary. Contact with a capillary can even trigger effects caused by gradients in interfacial tension, such as Marangoni convection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%